PENGEMBANGAN POTENSI ESTETIK DALAM PEMBELAJARAN MATEMATIKA SEKOLAH DASAR - Sari, Syafni Gustina; Jusar, Ira Rahmayuni (STKIP PGRI Sumatera Barat, 2016)
The purpose of this study is to produce pleasing module geometry and produce products aesthetically that are useful and marketable. From the results of the research conducted in subjects Mathematics Learning Class Advanced Class, this research is a research development by using the 4D model (define, design, develop, and disseminate). Phase in disseminate do not apply in this study. It was designed to see whether the module is valid or not. Then, do a trial expert, that expert Math Classroom Learning Module design and aesthetics in Advanced Mathematics Learning modules. Aspects which tested to the experts are the aspect of the material in the module, aspects of presentation, and aspects of advantages which is marketable. The results showed that the learning module of Math by experts already valid and aesthetically valuable. Based on the research result, it can be concluded that the modules of Classroom lectures Advanced Mathematics Learning Study Program Elementary School Teacher FKIP Bung Hatta University has a valid and aesthetically valuable.